Functional hyperthermia caused by obstructive sleep apnea syndrome: A case report. (September 2022) - Maita, Hiroki; Kobayashi, Tadashi; Akimoto, Takashi; Osawa, Hiroshi; Kato, Hiroyuki
A 47-year-old farm worker with diabetes mellitus, dyslipidemia, and hyperuricemia was referred to our hospital for a 3-month history of fever and malaise. He had no respiratory tract or abdominal symptoms, skin rashes, or joint pain. There was no change to his regular medication or pesticide exposure. Blood tests and echocardiography revealed no abnormalities. Whole-body computed tomography revealed a fatty liver; however, non-alcoholic steatohepatitis was excluded. We diagnosed the patient with functional hyperthermia. He had a history of snoring and weight gain, and we suspected the obstructive sleep apnea syndrome to be a stressor. Polysomnography revealed severe obstructive sleep apnea syndrome with an apnea–hypopnea index of 44.5. Continuous positive airway pressure was introduced; the axillary temperature decreased gradually and malaise was resolved. Functional hyperthermia should be considered a cause of fever with a negative inflammatory response. Obstructive sleep apnea syndrome can be a stressor for functional hyperthermia, which can be improved by interventions.